Conocimientos y aptitudes frente a. las Enfermedades de Transmisión Sexual entre Estudiantes de los Colegios No. 0756 y Ofelia Velásquez 1999 - Díaz Angulo, Wíller (1999)
Sexually Transmitted Diseases (STDs), follow an upward trend in Latin America specifically in Peru and the risk of transmission is greater among the poor and the knowledge and attitudes play an important role in preventing the same role for What the present study was conducted to determine the degree of knowledge and identify attitudes towards STDs among students of the Colleges N ° 0756 Pinto Recodo District, Province of Lamas (rural area) and Ofelia Velasquez College in the District of Tarapoto Province of San Martín (urban area). A comparative study was conducted, using the method of survey and interview, collecting data prospectively analyzing and interpreting data through descriptive and inferential statistical techniques. Indeed, the degree of knowledge of students of both schools was determined and the position taken by them are identified. The STDs most known by the students of both schools are gonorrhea and AIDS. The results reveal that students from the urban area (Ofelia Velasquez College) have greater knowledge and better attitudes towards Sexually Transmitted Diseases that students from rural (College No. 0756), verifying the hypothesis. It should be mentioned that the average degree of knowledge about STDs in both schools is bad, 7.717 N College "0756 and 10,075 College Ofelia Velasquez (Table 8). It was further found that the main factors influencing the degree of knowledge of STDs,. constitute the origin and means through which students reported STD slightly influential factors as gender and religion. The STDs most known by the students of both schools are gonorrhea and AIDS.